THE EFFECT OF ASTAXANTIN ADDITION IN ARTIFICIAL FEED ON INCREASING THE COLOR BRIGHTNESS OF SNAKEHEAD FISH (Channa maruliodes) - Khaidir, Muhammad; Sukendi, Sukendi; Putra, Iskandar (Asian Journal of Aquatic Sciences, 2024)
Snakehead fish (Channa maruliodes) is a freshwater fish that is increasingly popular among ornamental fish enthusiasts, especially because of its beautiful colors. Color brightness is an important factor in the culture of snakehead fish. This study aims to evaluate the effect of astaxanthin addition on increasing the color brightness of snakehead fish. This study used a completely randomized design (CRD) experimental method consisting of 4 treatments with 5 replications. The treatment used was the addition of Astaxanthin (AST) with doses of 0% (AST0), 1% (AST1), 3% (AST3), and 5% (AST5). The snakehead fish used had a weight size between 30.4-30.8 g/individual. The parameters measured in this study were the increase in color brightness, growth, feed conversion and efficiency, and the quality of the maintenance media. The results showed that the addition of astaxanthin in the feed had a significant effect on the level of color brightness, growth and feed utilization of snakehead fish (P <0.05). The best addition of astaxanthin was obtained in the AST5 treatment with a TCF value of 5.17, total carotenoids (136.68 ppm), absolute weight (23.00 g), absolute length (3.10 cm), specific growth rate (78.00%), feed conversion (4.35), and feed efficiency of 23.00%. These findings indicate the potential of astaxanthin in improving the quality of catfish culture.